Risks Associated with Celebrity Endorsements - An Empirical Analysis from Punjab - Singh, Maninder; Kaur, Kuldip (Indian Journal of Marketing, 2011)
Celebrity endorsement is the most useful and effective way to endorse the product in a competitive market because the celebrity has the source power to attract the consumer and change his attitude positively towards a particular product. Now-a-days, advertisers feel that a celebrity also compensates the endorsement in the absence of innovative ideas. It indicates that the presence of celebrity in endorsements itself has a great impact on consumers rather than any non-celebrity endorsement. But there are many potential risks related with the celebrity endorsements and these are harmful to the products and celebrities both. These risks also badly influence the image of the endorsed product and celebrity itself. The present study attempts to find out the risks associated with celebrity endorsements, on the basis of the primary data collected from 300 respondents of rural and urban areas of Amritsar, Ludhiana and Jalandhar districts of Punjab. Using multivariate techniques called Factor Analysis; factors are framed by grouping the variables that have correlation with each other. The results of the study indicate that there are five factors related to the potential risks of celebrity endorsements. These factors are: Multiple Product Endorsements, Financial Risk, Tarnished Brand Image, Misleading Advertisement and Negative Publicity.